Generation of a potent anti-PD-L1-CD47 bispecific antibody with a strong therapeutic and safety profile for cancer immunotherapy - Tang, Irene; Schwimmer, Lauren; Gu, Shenda; Wei Prior, Wei; Tran, Hieu Van; Chan, Allan; McClain, Anna; Fraser, Christopher C.; Sun, Chunyan; Si, Meimei; Wang, Guijiang; Zhao, Yunxia; et al. (Frontiers in Drug Discovery, 2023)
Cell surface molecules PD-L1 and CD47 are potent inhibitors of adaptive and innate anti-cancer immunity. We sought to generate a safe, therapeutic, bispecific antibody specifically targeting, and blocking both PD-L1 and CD47 inhibitory activity. Novel anti-PDL-1 and anti-CD47 antibodies with favorable inhibitory activity, were humanized and constructed into a unique bi-specific antibody intended for clinical use. Previous pre-clinical and clinical studies using anti-CD47 antibodies indicated anemia and thrombocytopenia as potential risks. QL401 is a PD-L1 x CD47 bispecific antibody engineered to reduce effect on red blood cells while retaining potent phagocytic activation of macrophages in vitro and delayed tumor growth in vivo. QL401 comprises three functional components: a PD-L1 binding Fab arm, a CD47 binding scFv arm, and a human IgG4 backbone. The PD-L1 binding arm provides both tumor targeting and blocking of PD-1 for reactivating T cells. The CD47 arm blocks the binding of SIRPα, while the IgG4 Fc retains Fc gamma receptor binding to provide a phagocytic signal. In preclinical efficacy studies, QL401 potently blocked SIRPα to promote phagocytosis of tumor cells with sub-nanomolar potency. In vivo efficacy studies in mouse xenograft tumor models showed QL401 to be comparable or superior to PD-L1 or CD47 monoclonal antibodies alone or in combination. In vitro safety evaluation of QL401 showed significantly reduced binding and phagocytosis of red blood cells, in contrast to CD47 monoclonal antibodies. In addition, QL401 did not induce hemagglutination. In non-human primates, QL401 was well tolerated up to 100 mg/kg without reduction of red blood cells or platelets below the normal range. QL401 is presently in a human phase I safety study.